2016
DOI: 10.1590/abd1806-4841.20164116
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dental material series from patients with dental prostheses and suspicion of delayed hypersensitivity

Abstract: BACKGROUNDPatients with oral sensitivity are common in our practice. Allergic contact dermatitis is one of the most frequent etiologies.OBJECTIVESEvaluate oral contact dermatitis using the Brazilian standard series and complementary dental series in patients using dental prostheses, with or without oral complaints. Determine specific dental Brazilian series.METHODSPatients using dental prostheses with or without oral complaints realized patch tests. Brazilian standard series and complementary dental series wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(19 reference statements)
0
3
0
3
Order By: Relevance
“…Gingivostomatitis is a disease of oral cavity that can also be associated with contact allergies after exposure to dental materials (e.g., metals or plastics in dentures), as it has been shown that stomatitis is associated with partial dentures and some dental metals (e.g., palladium, gold or manganese) ( Table 1) 7,39,40 . Gingivostomatitis as a reaction to acrylates is also possible (e.g., due to allergy to 2-hydroxyethyl methacrylate, HEMA, used in dentures).…”
Section: Review Of Oral and Perioral Diseases And Causative Allergensmentioning
confidence: 99%
“…Gingivostomatitis is a disease of oral cavity that can also be associated with contact allergies after exposure to dental materials (e.g., metals or plastics in dentures), as it has been shown that stomatitis is associated with partial dentures and some dental metals (e.g., palladium, gold or manganese) ( Table 1) 7,39,40 . Gingivostomatitis as a reaction to acrylates is also possible (e.g., due to allergy to 2-hydroxyethyl methacrylate, HEMA, used in dentures).…”
Section: Review Of Oral and Perioral Diseases And Causative Allergensmentioning
confidence: 99%
“…Most similar studies were focused on delayed hypersensitivity reactions in oral mucosal diseases by conducting patch tests 2,3,[11][12][13][14][15] , rather than by performing skin prick tests to detect immediate-type allergic reactions. What is more, previous research mainly investigated the role of contact allergens and inhalants in oral diseases, usually not determining common nutritive or additive allergens in oral and perioral diseases using skin prick tests [1][2][3] .…”
Section: Discussionmentioning
confidence: 99%
“…The key to getting an accurate diagnosis of allergy are skin patch and prick tests. Most of the previous studies were focused on delayed-type allergic reactions in oral diseases by performing patch testing but did not include tests for immediate-type reactions [1][2][3][10][11][12][13][14][15] . The objective of this study was to determine common nutritive and additive allergens in the prevalent oral and perioral diseases by using skin prick tests.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, há o risco de sensibilização cruzada ao formaldeído. Yoshimura et al (2016) desenvolveram uma pesquisa em pacientes que faziam uso de próteses que possuíam alguma queixa e com indivíduos que não apresentaram queixa de alergia oral, onde 54 pacientes foram submetidos a testes de sensibilidade e 34 apresentaram sensibilidade a pelo menos uma substância de teste odontológico. Dos pacientes que se queixam de incômodos na cavidade oral, 68% apresentaram resultados positivos.…”
Section: )unclassified
“…As reações do tipo I, também chamadas imediatas, na cavidade oral se manifestam como angioedema, sensação de ardor ou parestesia oral (Lugović-Mihić et al, 2020). As reações de hipersensibilidade tipo IV, também chamadas de tardia, são provocadas por haptenos e os sintomas para esse quadro são as reações liquenóides, eritema e estomatite (Yoshimura, 2016).…”
Section: Introductionunclassified